Combined bioaugmentation with anaerobic ruminal fungi and fermentative bacteria to enhance biogas production from wheat straw and mushroom spent straw. (July 2018) - Ferraro, Alberto; Dottorini, Giulia; Massini, Giulia; Mazzurco Miritana, Valentina; Signorini, Antonella; Lembo, Giuseppe; Fabbricino, Massimiliano
Graphical abstract: Highlights: ARF and F210 application allowed to increase CH4 cumulative productions and yields. Two-stage configuration showed higher CH4 production for both experimental scales. Higher CH4 maximum production was always achieved from digestion of wheat straw. Acetic acid was prevalent as soluble metabolite in all the experimental conditions. Cell density increase was predominantly observed in the two-stage configuration. Abstract: Bioaugmentation with anaerobic ruminal fungi and a pool of hydrogen-producing fermenting bacteria was tested on wheat straw (WS) and mushroom spent straw (MSS) with the aim of improving anaerobic digestion performance. Batch tests were set up to simulate a Bioaugmentation Anaerobic Digestion (BAD) treatment comparing single- (I-BAD) and two-stage (II-BAD) process configurations, at two reactor scales, 120 and 1200 ml (×10). In both cases, higher CH4 cumulative production was obtained in the II-BAD configuration on WS (65.1 ± 8.9 Nml and 922 ± 73.8 Nml respectively). The II-BADx10 tests allowed increasing CH4 production (≃290% and ≃330% on WS and MSS, respectively) when compared to the unaugmented condition. Final results highlighted the achievable advantages of the two stage configuration in terms of CH4 production enhancement. Microbial community investigations confirmed the efficiency of the bioaugmentation treatment and revealed that such a result was mainly related to the Methanosarcinales increase, mostly composed by Methanosaeta .